Malaysian Consumers Ethnocentrism: The Measurement Scale and Index - Noor Hasmini Abd Ghani; Nik Kamariah Nik Mat (International Review of Management and Marketing, 2017)
The government has revived its campaign for “Buy Malaysian Goods” in 2010 after its last campaign in 2009, in due to an increase of foreign competition. The campaign is to remind consumers to be ethnocentric and patriotic when purchasing product and services. This study attempts to specify the demographic profile of ethnocentric consumers; to validate the scale of ethnocentrism and its antecedents, and; to determine ethnocentrism index for Malaysian consumers. From the literature, 7 antecedents of customer ethnocentrisms were identified. Each variable is measured using 7-point Likert-scale: culture openness (6 items), conservatism (6 items), collectivism (6 items), patriotism (6 items), control belief (10 items), interest in foreign travel (4 items), and attitude toward local product (8 items). From 1000 questionnaires distributed to households, 486 were returned representing 48.6 percent response rate. The EFA of exogenous latent variables shows that most items conform back into its underlying components, thus, the instruments seem to surpass the convergent validity test. EFA of ethnocentrism however, diverts into two components: ethnocentrism (11) and animosity (6). The findings indicate support for validity of measurement models of all variables utilized. But, the result revealed that the ethnocentrism index for Malaysian consumers is middle category index.